CURRENT STATE OF POPULATIONS OF THE MAIN COMMERCIAL FISH SPECIES OF THE SMALL ARAL SEA (Experimental biology, 2021)
The Aral Sea was one of the main commercial basins until the 80s of the last century. However, intensive water management activities aimed at regulating the upper reaches of the Syrdarya and Amudarya rivers, which were the main sources of water supply in the Aral Sea, led to a decrease in the water level and the sea was initially divided into two reservoirs: Small and Large.As a result, huge damage was caused to the fishing industry of the region. And only after more than 20 years, a decision was made to restore the Aral Sea, by building a dam, in order to block the channel connecting the Small Aral with the Big Sea. In 2005, the construction of the Kokaral separation dam was completed.The basis of the fishery is: bream (Abramis brama), zander (Sander lucioperca), pike (Esox lucius), asp (Aspius aspius), carp (Cуprinus caspio)